Sustainable Management Accounting - Conceptual and Reporting Issues Źródło - Gabrusewicz , Tomasz (Studia Oeconomica Posnaniensia, 2014)
What is sustainability? It is sometimes used as an alternative for the term corporate social responsibility; and the most widely accepted definition of sustainability that has emerged over the years is the "triple bottom-line" consideration of: 1) economic viability, 2) social responsibility, 3) environmental responsibility. While environmental considerations are often the focus of attention, the triple-bottom-line definition of sustainability is a broad concept. In addition to the preservation of the physical environment and stewardship of natural resources, sustainability considers the economic and social context of doing business as well as also encompassing the business systems, models and behaviours necessary for long-term value creation. The purpose of this article is to analyse the concept of sustainable accounting and reporting in management accounting in the light of the principles of sustainable development theory.